2019
DOI: 10.1177/0020731419847589
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities in Following Official Guidelines on Healthy Diet During the Period of Economic Crisis in Spain

Abstract: In Spanish society, social inequalities continue in connection with diet; however, no data examines whether these inequalities altered during the period of economic crisis. This article aims to analyze trends in inequalities related to adherence to government guidelines concerning healthy diet during the period of economic crisis based on the data obtained from the National Health Surveys conducted by the National Statistics Institute. The approach involves studying first the data from the 2006 survey, shortly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 32 publications
(52 reference statements)
4
40
0
Order By: Relevance
“…It is worth noting that occasional lamb consumption increased between 2004 and 2014, perhaps as a result of the higher price of this meat relative to possible substitutes, its aspect, and also its traditional association with consumption on special occasions or festivities, as suggested by Blasco, et al [ 48 ], all within a setting of reduced lamb meat consumption in the EU [ 1 , 2 , 3 , 4 , 8 ]. The results corroborate those of Díaz-Méndez and García-Espejo [ 34 ], who concluded that, in times of crisis, high-priced products and those for which medical guidelines recommend reduced intake (as is the case of lamb meat) suffer a notable reduction in consumption. Some other factors, such as the shifting from the consumption of red meat towards healthier white meat [ 6 , 7 ] can be also partially responsible for this reduction in the consumption of lamb meat.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It is worth noting that occasional lamb consumption increased between 2004 and 2014, perhaps as a result of the higher price of this meat relative to possible substitutes, its aspect, and also its traditional association with consumption on special occasions or festivities, as suggested by Blasco, et al [ 48 ], all within a setting of reduced lamb meat consumption in the EU [ 1 , 2 , 3 , 4 , 8 ]. The results corroborate those of Díaz-Méndez and García-Espejo [ 34 ], who concluded that, in times of crisis, high-priced products and those for which medical guidelines recommend reduced intake (as is the case of lamb meat) suffer a notable reduction in consumption. Some other factors, such as the shifting from the consumption of red meat towards healthier white meat [ 6 , 7 ] can be also partially responsible for this reduction in the consumption of lamb meat.…”
Section: Resultssupporting
confidence: 88%
“…In a study conducted in Spain, Díaz-Méndez and García-Espejo [ 34 ] found that during the 2007–2017 economic crisis the consumption gap converged downwards, regardless of income, in the case of the most expensive products and those for which medical guidelines recommend reduced intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendations tried to avoid creating dietary advice that people could perceive as a limitation or imposition on individual freedom of choice or in disagreement with the cultural context [49,50,51]. This is a proposal for a comfortable path that contributes to building healthier and more sustainable food patterns [49,52] and recovering a traditional diet closer to the Mediterranean diet—a dietary pattern culturally sensible and affordable for many people in the country [53,54,55], although supportive policies for implementation that consider inequalities will be required. The Mediterranean diet can be considered as the most studied and well-known dietary pattern in the world [56].…”
Section: New Food-based Dietary Guidelines For the Spanish Populationmentioning
confidence: 99%
“…Sixteen studies investigated intake of sources of proteins (26,29,30,37,38,41,45,47,48,50,53,54,60,61,64,65). While most studies examined consumption of protein sources separately, share of calories from poultry and sh increased while calories from red meat and nuts decreased in the UK (47).…”
Section: Food Intakementioning
confidence: 99%